VOLUMES OF GENERA AND SPECIES COMPOSITION OF ORIBATIDA (ACARIFORMES, ORIBATIDA) OF THE INTERNAL MOUNTAIN DAGESTAN - G. M. Abdurakhmanov; E. Z. Davudova (Юг России: экология, развитие, 2014)
This work is based on research and materials collected from 2000 to 2012, with the application of the method of selection of soil samples, according to the methodology of the quantitative survey. As a result of the conducted researches on the territory of the internal mountain Dagestan found 190 species of Oribatida belonging to 83 generations.